CEO replacement under private information - Roman Inderst; Holger Müller (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2009)
We study a model of “information-based entrenchment” in which the CEO has private information that the board needs to make an efficient replacement decision. Eliciting the CEO's private information is costly, as it implies that the board must pay the CEO both higher severance pay and higher on-the-job pay. While higher CEO pay is associated with higher turnover in our model, there is too little turnover in equilibrium. Our model makes novel empirical predictions relating CEO turnover, severance pay, and on-the-job pay to firm-level attributes such as size, corporate governance, and the quality of the firm's accounting system.
urn:nbn:de:hebis:30-72972
Keywords: 330